Abrasive wear of FeCr (M7C3 - M23C 6) reinforced MMCs - Yilmaz, Osman; Aksoy, Mustafa (My University, 2002)
The effects of volume fraction, particle size and sintered porosity of FeCr (M7C3 -M23C6) participates on the abrasive wear resistance of powder metallurgy (P/M) Fe alloy MMCs have been studied over different abrasive conditions. It was seen that the abrasive wear rates of composites increased with increase in FeCr volume fraction at the test performed over 80 grades SiC abrasive paper, but it decreased for the tests conducted over 220 grade SiC abrasive paper. Furthermore, the wear rates decreased with increase in FeCr size for the composites containing the same amount of FeCr. Hence it is deduced that, Fe alloy composites reinforced with larger FeCr size are more effective against abrasive wear than those reinforced with smaller FeCr size. At the same time the results show that, the beneficial effects of hard FeCr particulates on wear resistance far surpassed that of the sintered porosity in the P/M metal matrix composites (MMCs). Nevertheless, the fabrication of composites containing soft particles as graphite or copper favors a reduction in the friction coefficient, and increases matrix hardness of composites. For this reason graphite and copper was used at matrix in different amount to detect their effect on wear resistance. The increase in graphite and copper volume fraction formed additional phases, which has high hardness and wear resistance. Finally, it was seen that wear rate of the composites decreased in the considerable amount with graphite and copper addition.
Proceedings of the 3rd International Powder Metallurgy Conference -- 4 September 2002 through 8 September 2002 -- Ankara -- 62829
Keywords: Abrasion; FeCr; Microstructure; MMC; Wear Mechanism